Mengukur Efisiensi Investasi Daerah: Analisis Icor Kabupaten Bandung dan Proyeksi Tahun 2025–2030 - Daniel Simamora (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to analyze investment efficiency in Bandung Regency from 2011 to 2024 and project it for the years 2025 to 2030. Investment efficiency is measured using the Incremental Capital-Output Ratio (ICOR) based on data from Gross Regional Domestic Product (PDRB) and Gross Fixed Capital Formation (PMTB) at constant 2010 prices. Forecasting is performed using the Autoregressive Integrated Moving Average (ARIMA) model. The analysis results show fluctuating ICOR values, reflecting annual variations in investment efficiency. Projections for 2025–2030 indicate a potential decline in efficiency, which signals important considerations for regional development planning. The findings highlight the need for the Investment and Integrated One-Stop Service Office (DPMPTSP) to use ICOR as a key performance indicator when formulating more effective and efficient investment policies to support quality economic growth in Bandung Regency. This study recommends improving future investment policies by utilizing the ICOR indicator to monitor and evaluate the effectiveness of regional investments.